2015
DOI: 10.1038/ejhg.2015.241
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genotyping reveals RPE65 as the most frequently mutated gene in Leber congenital amaurosis in Denmark

Abstract: Leber congenital amaurosis (LCA) represents the most severe form of inherited retinal dystrophies with an onset during the first year of life. Currently, 21 genes are known to be associated with LCA and recurrent mutations have been observed in AIPL1, CEP290, CRB1 and GUCY2D. In addition, sequence analysis of LRAT and RPE65 may be important in view of treatments that are emerging for patients carrying variants in these genes. Screening of the aforementioned variants and genes was performed in 64 Danish LCA pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 43 publications
3
57
1
1
Order By: Relevance
“…8 These genes have been shown to encode proteins with a diverse range of retinal functions, including phototransduction, the visual cycle and photoreceptor development/integrity (table 1, figure 1). [9][10][11] Given recent advances in understanding of the molecular basis of these disorders and the ongoing clinical trials of novel therapies, we herein review the clinical characteristics, animal models and pathophysiology of LCA/EOSRD, prioritising the more common genotypes and/or those closest to intervention.…”
Section: Introductionmentioning
confidence: 99%
“…8 These genes have been shown to encode proteins with a diverse range of retinal functions, including phototransduction, the visual cycle and photoreceptor development/integrity (table 1, figure 1). [9][10][11] Given recent advances in understanding of the molecular basis of these disorders and the ongoing clinical trials of novel therapies, we herein review the clinical characteristics, animal models and pathophysiology of LCA/EOSRD, prioritising the more common genotypes and/or those closest to intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biallelic RPE65 mutations contributed to approximately 3.0% (8/269) of LCA and 0.8% (18/2133) of HRD cases. Clinically, diseases in 13 of the 18 families could be classified as LCA or EORD, which are common phenotypes previously reported to be associated with RPE65 mutations (Gu et al 1997;Marlhens et al 1997;Morimura et al 1998;Thompson et al 2000;Simovich et al 2001;Yzer et al 2003;Booij et al 2005;El Matri et al 2006;Simonelli et al 2007;Li et al 2009;Xu et al 2012;Kabir et al 2013;Verma et al 2013;Astuti et al 2016;Katagiri et al 2016). In the remaining five families with biallelic RPE65 mutations, we unexpectedly found that the phenotypes were FA-like changes in four families and high hyperopia in one family.…”
Section: Discussionmentioning
confidence: 91%
“…Detected variants were amplified, Sanger sequenced, and finally validated with independent polymerase chain reactions (PCR). 26 The German cohort was analyzed using direct Sanger sequencing, APEX, and next-generation sequencing.…”
Section: Genetic Analysismentioning
confidence: 99%